Anger fosters action. Fast responses in a motor task involving approach movements toward angry faces and bodies - Valk, Josje M. de; Wijnen, Jasper G.; Kret, Mariska E. (Frontiers in Psychology, 2015)
Efficiently responding to others’ emotions, especially threatening expressions such as anger and fear, can have great survival value. Previous research has shown that humans have a bias towards threatening stimuli. Most of these studies focused on facial expressions, yet emotions are expressed by the whole body. Body language contains a direct action component, and activates action preparation areas in the brain more than facial expressions. Hence, biases towards threat may be larger following threatening bodily expressions as compared to facial expressions. The current study investigated reaction times of movements directed towards emotional bodies and faces. For this purpose, a task was developed where participants were standing in front of a computer screen on which angry, fearful and neutral faces and bodies were presented which they had to touch as quickly as possible. Results show that participants responded faster to angry than to neutral stimuli, regardless of the source (face or body). No significant difference was observed between fearful and neutral stimuli, demonstrating that the threat bias was not related to the negativity of the stimulus, but likely to the directness of the threat. Whereas fearful stimuli might signal an environmental threat that requires further exploration before action, angry expressions signal